International Legal Instruments in Responding to Human Trafficking - Arifin, Ridwan; Lemuel, Yehezkiel; Nte, Ngaboawaji Daniel (Lentera Hukum, 2021)
Human trafficking grows and develops rapidly, with various motives and types of crimes. Various obstacles are faced in handling human trafficking cases, ranging from inadequate legal instruments to weak law enforcement. This study overviewed the international legal instrument on human trafficking cases, following the identification of the recent forms and issues in enquiring how international legal instruments deal with human trafficking. This study used legal research method by referring to international laws as the source of law in compiling this human trafficking research. This study found that various instruments and international cooperation have dealt with human trafficking cases. However, in various related studies, these different legal instruments did not have a clear and binding force when the issue occurs in the domestic state. In addition, human trafficking in various legal instruments also had many types, and all of them are interrelated. This study highlighted and concluded that in making various international legal instruments effective in this case, more intensive international cooperation was needed, both regionally and globally. KEYWORDS: Human Trafficking, Labor Human Rights, Criminal Law.